Pohl's Introduction to Physics - Lüders, Klaus; Pohl, Robert O. (Springer, 2017)
This classic textbook on experimental physics, written by Robert W. Pohl to accompany his famous lecture courses, served generations of physics and other science majors, not only in his native Germany, and was for many years a standard textbook. Pohl's lucid and memorable style and his consistent use of vivid demonstration experiments made his textbooks unique in their time. This completely revised and updated modern edition retains his style and clarity in an up-to-date format. The accompanying videos document the original demonstrations and add many modern touches, bringing to life the numerous illustrations in the book and providing an instructive and motivating complement to the text. They are linked to the corresponding topics in the text and can be accessed directly online from the e-book version. Volume 1 covers elementary mechanics, acoustics (vibrations and waves) and thermodynamics. The exercises provide an aid to understanding the material as well as complementary information. This book addresses students of physics and of other natural sciences and engineering, but also teachers and lecturers, who will profit from Pohl's many demonstration experiments, and other interested readers who want to gain an understanding of the fundamentals of physics from an experimental viewpoint.